Cilioretinal arteries: incidence in a 1110 patients’sample - Pannarale, Luigi; Arrico, Loredana; Formisano, Martina (Italian Journal of Anatomy and Embryology, 2018)
The central retinal artery, supplies retinal vasculature. In some cases, a part of retinal cir- culation is supplied by a cilioretinal artery [1]. Cilioretinal arteries take rise from a posterior ciliary artey [2]. If retinal vascular occlusion occurs, the presence of a cilioretinal artery can be a significant factor influencing visual morbidity [3]. Studies on the frequency of this anatomical anomaly are limited in number and most of them take into consideration a small number of subjects. Largest two studies are Wang et al. (1991) [4], on 2050 patients, published only in Chi- nese language, and Liu et al (2011) on 2500 patients [5]. We examined the fundus photographies of 1110 patients between the age of 7 and 100, with an average of 51 years old.Observations were made through the use of a high definition confo- cal scanner fundus camera (Eidon). This instrument provides high resolution images in a short time even through an undilated pupil. These characteristics have been advantageous for obtain- ing viable images of the fundus oculi even in the pediatric patients. Cilioretinal arteries were found in 380 patients (34.2%). Among 380 patients, 178 (47% ) were males and 202 (53%)were females. Of these patients, 97 (25,5 %) presented this anatomical variant in both eyes and 283 (74,5%) in only one eye. This variant was mostly present in the right eye (64,7 %of the right eyes and 35,3%of the left eyes), and 95 patients (25%) had more than one cilioretinal artery. Finally, in 330 cases (87%) the vessels were temporal, in 19 (5%) were only nasal and in 30 cases (8%) the patients had both temporal and nasal cilioretinal arteries. This is one of the largest studies in literature. Our results are obtained with a non invasive technique. Nevertheless, inci- dence of cilioretinal arteries in our study is comparable with that obtained by fundus fluores- cein angiography, normally considered the most accurate method to visualize retinal vessels. Our non invasive approach is a base for further investigations.